(untitled) (Research, Society and Development, 2021)
This study aims to analyze some notes about entrepreneurship and startups, especially with regard to economic growth and the solution of common problems. In this perspective, this article, through exploratory research, of a qualitative nature, deductive method, collection of documentary and bibliographic data, proceeded in order to carry out a detailed analysis of the normative framework it deals with about startups. Nevertheless, it also clarified the lack of any differentiation or privileges granted to this business species, applying to it all the legal dictates of the most diverse legal fields, from labor, tax, civil, criminal and business. Thus, in view of the exposed problem, it was sought to elucidate the need of the State, based on legal security and economic growth, to implement specific treatment for startups, considering that they have great potential for contributing to our country, be it because they will generate income, jobs, revenue for the State, movement of the economy, among others.